Comparison of finite helical axes of normal and anatomically designed prosthetic knees. (May 2019) - Konda, Shoji; Tomita, Tetsuya; Yamazaki, Takaharu; Oda, Kosaku; Nakajima, Mikio; Nakane, Kunio; Kono, Kenichi; Fujito, Toshitaka; Yoshikawa, Hideki; Sugamoto, Kazuomi
Abstract: Background: Describing three-dimensional joint motion using the finite helical axis has an advantage in understanding unknown coupling motion in prosthetic knee joints. We aimed to examine the differences in the orientations of finite helical axis of normal and anatomically designed cruciate-retaining and posterior-stabilized prosthetic knees after total knee arthroplasty. Methods: Ten normal, 40 cruciate-retaining prosthetic knees of 33 patients and 19 posterior-stabilized prosthetic knees of 14 patients enabling to flex > 120° were analyzed during a squatting motion with deep knee bending. The motion was recorded by a fluoroscopic imaging system, and the pose of the bone and prostheses were determined by an image registration technique. The finite helical axes were calculated using 30° window. Findings: The finite helical axis in the early flexion phase of the normal knees had a greater inferior inclination (mean − 19.0° (SD 7.2°)) than those of the cruciate-retaining (mean − 1.7 (SD 5.0°)) and posterior-stabilized (mean − 2.9° (SD 5.5°)) prosthetic knees ( p  < 0.001), and became almost horizontal and constant in the mid to deep flexion phases. In contrast, the cruciate-retaining and posterior-stabilized prosthetic knees demonstrated slightly inclined and almost constant vertical angles throughout the all phases. Interpretation: These results demonstrate that, in the normal knee, a clear coupling motion occurs during the early flexion phase. For the cruciate-retaining and posterior-stabilized prosthetic knees, an unclear coupling motion exists during all phases. These results suggest that the physiological motion is not possible to reproduce using shape-guided motion only even in an anatomically designed prosthetic knee. Highlights: Finite helical axis is advantageous to understand complex knee joint motion. Finite helical axes during squatting were examined by fluoroscopy in normal and prosthetic knees. Normal knees showed clear coupling motion in flexion and rotation in initial flexion. Prosthetic knees showed unclear coupling motion throughout all the phases. Phase-dependent changes in coupling motion may not reproducible in prosthetic knees.